Concerns, perceived impact, practices, preventive measures, and stress among healthcare workers during COVID-19 pandemic in Malaysia - Pahrol, Muhammad Alfatih; Ismail, Rohaida; Mohamad, Nadia; Lim, Yin Cheng; Muhamad Robat, Rosnawati; Rajendiran, Sakshaleni; Syed Abu Thahir, Syahidiah; Abdul Shakor, Ameerah Su'ad; Ramly, Nurfatehar; Shaharudin, Rafiza (Frontiers in Public Health, 2023)
Healthcare workers (HCWs) have been continually exposed to COVID-19 patients and are at higher risk of contracting the disease. Their psychological health is important for overall well-being and productivity, which could lead to a reduction in human errors during the pandemic crisis. This study aimed to measure the level of concerns, work practices, adequacy of preventive measures among HCWs and the impacts on their life and work, including mental health status during the second wave of the COVID-19 pandemic in Malaysia. A online questionnaire was distributed randomly to 1,050 HCWs from Ministry of Health facilities in the Klang Valley who were involved directly in managing or screening COVID-19 cases from May to August 2020. The questionnaire was divided into five domains, which were on concerns, impact on life and work, practice, perceived adequacy of preventive measures, and Revised Impact of Event Scale (IES-R). Logistic regression was used to identify sociodemographic predictors of the 5 domains. A total of 907 respondents (86.4%) participated in this survey. About half of the respondents had a low concern (50.5%), most of them had a good practice (85.1%), with 67.5% perceived there were adequate preventive measures, and they perceived the outbreak had low impact (92%) on their life and work. From the IES-R domain, 18.6% of respondents potentially suffered from posttraumatic stress disorder (PTSD). During the second wave of the COVID-19 outbreak in Malaysia, HCWs practiced high levels of precautions and preventive measures because they were aware of the risk of infection as an occupational hazard. With the adequate implementation of policy and control measures, the psychological well-being of the majority HCWs remained well and adequately supported.